2016
DOI: 10.1128/aem.00393-16
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characteristics and Substrate Degradation Pattern of a Novel Exo-Type β-Agarase from the Polysaccharide-Degrading Marine Bacterium Flammeovirga sp. Strain MY04

Abstract: Exo-type agarases release disaccharide units (3,6-anhydro-L-galactopyranose-␣-1,3-D-galactose) from the agarose chain and, in combination with endo-type agarases, play important roles in the processive degradation of agarose. Several exo-agarases have been identified. However, their substrate-degrading patterns and corresponding mechanisms are still unclear because of a lack of proper technologies for sugar chain analysis. Herein, we report the novel properties of AgaO, a disaccharide-producing agarase identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 41 publications
0
21
1
Order By: Relevance
“…The K m of rAgaM1 (1.82 mg ml −1 ) was lower than most of the agarases reported previously, such as AgaML (4.6 mg ml −1 ) , AgaJ11 (21.42 mg ml −1 ) , and strain NTa agarase (11.3 mg ml −1 ) . This Michaelis constant suggested a high affinity of rAgaM1 for agarose.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The K m of rAgaM1 (1.82 mg ml −1 ) was lower than most of the agarases reported previously, such as AgaML (4.6 mg ml −1 ) , AgaJ11 (21.42 mg ml −1 ) , and strain NTa agarase (11.3 mg ml −1 ) . This Michaelis constant suggested a high affinity of rAgaM1 for agarose.…”
Section: Discussionmentioning
confidence: 57%
“…MY04 are 45 °C and 7.0, respectively. However, when the temperature is over 50 °C or the pH is over 8.0, about 80% of the activity is lost . The optimum pH of AgWH50C is 6.0, but only 28% of the activity is detected at pH 7.0, and the activity is completely lost at other pH values .…”
Section: Discussionmentioning
confidence: 98%
“…AOS has received increasing attention because of its physiological and biological functions beneficial for the health of human beings ( Han et al, 2016 ; Gao et al, 2017 ). However, to our best knowledge, no study has reported on the AGA amelioration activities of AOS.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 140 amino acid peptides with unknown function were truncated from the C-terminal of AgaG4, causing a 35-fold increase of agarase activity ( Liu, 2015 ); however, the removal of 60 amino acids from AgaM1 in this study decreased the activity and stability of this agarase. Conversely, the truncated AgaO lost all the agarase activity ( Han et al, 2016 ). Without the information of protein structures, these differences cannot be scientifically and detailly explained.…”
Section: Discussionmentioning
confidence: 99%